Bio-Sensing of [S & N]–Heterocyclic Carbene Corrosion Inhibitors by Sn–Embellished on the Al-Mg Crystal Surface: A DFT Study - (:unkn) unknown (AMG Transcend Association, 2024)
The partial electron density states (PDOS) have described an obvious charge accumulation between the Al–Mg alloy and the doped atom of Sn through the recognition of the conduction band region. The physicochemical properties of adsorption on the nanosurface are one of the fundamental parameters for determining and choosing the Langmuir adsorption through IR, NMR, UV-VIS, and HOMO/LUMO and charge distribution results. Therefore, in this article, the ONIOM approach has been performed with a three-layered level of the high level of DFT method using EPR-III, 6-31+G (d,p) and LANL2DZ basis sets by the physicochemical software of Gaussian 16 revision C.01, a medium semi-active part that includes important electronic contributions, and a low-level part that has been handled using MM2 force field approaches. Comparing to 〖∆G〗_ads^o amounts approved a good agreement among computed results, as well as the correctness of the selected isotherm for the adsorption process of benzotriazole → Al-Mg-Sn, 2-mercaptobenzothiazole→ Al-Mg-Sn, 8- hydroxyquinoline → Al-Mg-Sn, and 3-amino-1, 2, 4-triazole-5-thiol → Al-Mg-Sn. The infrared spectra for each of these inhibitor-metal alloy surface have been introduced in the frequency range around 500cm-1-4500cm-1 for benzotriazole → Al-Mg-Sn, 2-mercaptobenzothiazole → Al-Mg-Sn, 8- hydroxyquinoline → Al-Mg-Sn and 3-amino-1, 2, 4-triazole-5-thiol → Al-Mg-Sn with the sharpest peak approximately around 1750cm-1 for benzotriazole → Al-Mg-Sn, 2000cm-1 for 2-mercaptobenzothiazole → Al-Mg-Sn, 3000cm-1 for 8- hydroxyquinoline → Al-Mg-Sn and 3900cm-1 for 3-amino-1, 2, 4-triazole-5-thiol → Al-Mg-Sn. Nuclear magnetic resonance has certainly focused on aluminum shielding in the intra-atomic interaction with aluminum, magnesium, and silicon and simultaneously interatomic interaction with other atoms in organic inhibitors through a variety of high, medium, and low layers of ONIOM methods. Al-Sn(14), Al-Sn(19), and Al-Sn(21) in the Al-Mg-Sn alloy surface with the highest fluctuation in the shielding tensors of NMR spectrum generated by intra-atomic interaction direct us to the most influence in the neighbor atoms generated by interatomic reactions of N→Al, O→ Al, S→ Al through the coating and adsorbing process of Langmuir adsorption. Moreover, based on the computed amounts of UV-VIS spectra for benzotriazole, mercaptobenzothiazole, 8-hydroxyquinoline and 3-amino-1, 2, 4-triazole-5-thiol adsorbed on the Al-Mg-Sn alloy surface, there are maximum adsorption bands between 500nm-2000nm wavelengths for these organic heterocyclic inhibitors joint metal alloy which has illustrated a certain peak with approximately 1000nm wavelength.